Partial oxidation treatment of waste polyvinyl chloride in critical water: Preparation of benzaldehyde/acetophenone and dechlorination. (20th September 2018) - Qi, Yingying; He, Jiahuan; Xiu, Fu-Rong; Nie, Wenjie; Chen, Mengjun
Abstract: In this work, a partial oxidation treatment process in critical water was developed for high-efficiency dechlorination of waste polyvinyl chloride and the recovery of high value-added chemical feedstock. The partial oxidation treatment of waste polyvinyl chloride was performed at the temperature range of 200–400 °C with the mass ratio of 32 (waste polyvinyl chloride-to-oxygen). Fourier Transform Infrared Spectroscopy and Gas Chromatography-Mass Spectrometer were utilized to characterize solid residue and oil products. The chlorine in aqueous phase was measured by ion chromatography to determinate the dechlorination efficiency. The results indicated that 85.5% of the chlorine in waste polyvinyl chloride could be transferred into aqueous phase at 250 °C, and approximately 95% could be transferred at 300 °C. The temperature of critical water had a significant effect on chemical composition of oil products of waste polyvinyl chloride after the partial oxidation treatment. Two important chemical feedstock, benzaldehyde and acetophenone, could be selectively prepared from waste polyvinyl chloride by the partial oxidation treatment in critical water at lower temperature condition. The summation of the relative peak area of benzaldehyde and acetophenone from the results of Gas Chromatography-Mass Spectrometer could reach 91.74% and 91.68% at 300 °C and 350 °C. The further increase of partial oxidation treatment temperature could enhance the reactivity of oxygen involved in the system and initiate more side reactions, resulting in that many impurity compounds were generated, including phenol/phenol derivatives, naphthalene, aliphatic alkanol, and cyclanone. The purity of benzaldehyde and acetophenone in oil products decreased when the partial oxidation treatment temperature exceeded 350 °C, and the additional value of decomposition products was lowered. This result showed that the partial oxidation treatment of waste polyvinyl chloride in critical water was beneficial for both dechlorination and resources recovery. Graphical abstract: Image Highlights: An eco-friendly POT process in CW is proposed for treatment of waste PVC. Benzaldehyde and acetophenone can be selectively prepared from waste PVC by POT. POT has a high-efficiency dechlorination for waste PVC. Cl-free oil products can be obtained from waste PVC by POT process in CW.